The Degree of Satisfaction of Teachers of Deaf Students with the Use of Educational Platforms in Teaching their Students during the Corona Pandemic - Al-Momani, Randa Mousa; Majali, Areen A.Q Bajes AL Jadeed (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to identify the degree of satisfaction of teachers of deaf students with the use of educational platforms in teaching their students during the Corona pandemic. Methods: The study employed a descriptive approach, focusing on male and female teachers in deaf schools in the Capital Governorate during the second semester of the 2021/2022 academic year. Selection involved a simple random method from two schools, Marka School for People with Hearing Challenges and Al-Amal School for the Deaf, totaling 80 teachers. A 13-item questionnaire with verified validity and reliability was utilized, employing a five-point Likert scale. Results were assessed using three levels: low (1-2.33), medium (2.34-3.67), and high (3.68-5). Results: The results of the study showed that the degree of satisfaction of teachers of deaf students with the use of educational platforms in teaching their students during the Corona pandemic was at a moderate level with a mean of (3.08). The results also indicated that there were no statistically significant differences at the level of significance (α ≤ 0.05) in the degree of the teachers of deaf students’ satisfaction, and is attributed to each of the variables, which are gender, educational qualification, and years of experience. Conclusions: The study recommends that educational platforms should cater to the needs of deaf students by offering a unified sign language dictionary, suitable evaluation tools, and visual explanations for courses to facilitate their learning process.